2020
DOI: 10.1097/sla.0000000000003051
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability (MSI) as an Independent Predictor of Pathologic Complete Response (PCR) in Locally Advanced Rectal Cancer

Abstract: Objective: The relationship between microsatellite instability (MSI) and response to neoadjuvant chemoradiation in rectal cancer is not well understood. Background: We utilized the National Cancer Database (NCDB) to investigate the association between MSI and pathologic complete response (pCR) in this patient population. Methods: We analyzed 5086 patients between 2010 and 2015 with locally advanced rectal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 32 publications
4
76
3
Order By: Relevance
“…In contrast, other studies have reported that patients with MSI-H or dMMR rectal cancer had higher survival rates (16,30). These contradictory results regarding MSI as a predictive factor may be attributable to the mixed rectal cancer phenotypes with patients harboring various concomitant mutations in different genes such as BRAF, KRAS, or other cancer pathway genes that generally show poor prognosis (15,29). In the meantime, the MSI status from surgically resected specimens after neoadjuvant CRT was not associated with survival outcomes in the present study.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast, other studies have reported that patients with MSI-H or dMMR rectal cancer had higher survival rates (16,30). These contradictory results regarding MSI as a predictive factor may be attributable to the mixed rectal cancer phenotypes with patients harboring various concomitant mutations in different genes such as BRAF, KRAS, or other cancer pathway genes that generally show poor prognosis (15,29). In the meantime, the MSI status from surgically resected specimens after neoadjuvant CRT was not associated with survival outcomes in the present study.…”
Section: Discussionmentioning
confidence: 87%
“…However, the role of MSI as a predictive factor in rectal cancer has not been confirmed (29). Some studies have reported that MSI-H was independently associated with poor pCR rates after neoadjuvant CRT (15), and had inferior survival outcomes for rectal cancer (14). In contrast, other studies have reported that patients with MSI-H or dMMR rectal cancer had higher survival rates (16,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, early-stage colorectal adenocarcinomas testing positive for MSI may carry a favorable prognosis and therefore do not require adjuvant chemotherapy [3][4][5] . Some studies suggest that these tumors are more prone to be sensitive to 5-FU chemo(radio)therapy, although this finding is controversial [6][7][8][9][10] . Even if a significantly decreased likelihood of pathologic complete response (pCR) has been demonstrated for dMMR patients after chemoradiation 6 in the largest sample-sized study, no study has been reported to investigate the association of MMR status with survival and response to neoadjuvant radiotherapy (NRT) with a comparison of patients receiving neoadjuvant chemotherapy (NCT) with or without radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…-L1 programmed cell death-Ligand 1, dMMR mismatch repair deficient, MSI-H microsatellite high instability According to the article of Carr et al[41], lifestyle can affect the molecular pathological types of colorectal cancer and statistics show that moderate and high alcohol consumption is associated with an increased risk of MSI-H colon cancer. MSI can be used as a significant molecular marker for prognosis and adjuvant therapy of CRC[42]. MSI has different effects…”
mentioning
confidence: 99%